Perspektif Al-Qur’an Tentang Sel Saraf Dalam Kajian Integrasi Agama Dan Sains - Siti Nafilatul Rohmah; Kholisatul Umami; Ifka Ramadhani; Siti Andini; Alfina Wildatul Fitriyah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Humans are God's perfect creation. Perfection lies in reason. Apart from intelligence, humans also have a brain as the control center for all human activities. The aim of this research is to examine and discover more deeply about human nerve cells from the perspective of the Koran. This research uses qualitative methods and produces descriptive data through a literature approach. The main sources start from secondary sources including books or journals related to the concept of nerve cells according to religious and scientific views. There are several verses scattered in the surahs of the Koran regarding nerve cells. The word "Naashiyah" in this verse means forelock. Scientific facts about the crown is the part of the forebrain that functions as a controller, memory and decision maker, which is known as Frontal lobe. The information from these verses is true that the forelock is the place where decisions are made and is the measuring point for right or wrong decisions taken. Therefore, Al-Quran information and scientific facts from research results are integrated with each other and show harmony.